2022
DOI: 10.1002/chem.202104497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intermolecular Non‐Covalent Interactions in a CuI8PdII1 Discrete Assembly: Conformers’ Geometries and Stimuli‐Sensitive Luminescence Properties

Abstract: A new highly solid-state luminescent phase of a previously reported weakly luminescent Cu I 8 Pd II 1 dicationic assembly is reported revealing the high geometrical versatility of this moiety that importantly alters its luminescent properties. This very minor new species B c is based on a different conformer scaffold than the one encountered in the previously reported B o form and, essentially differs from B o by displaying shorter Cu I -Cu I intermetallic distances. DFT calculations allow concluding that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 112 publications
1
12
0
Order By: Relevance
“…Costuas, Yam, and Lescop have reported a different approximation to the building of highly luminescent supramolecular moieties containing Pd(II) centers [ 109 , 110 ]. In these cases, the tetranuclear Cu(I) derivative {[Cu 2 (μ-dppm) 2 ] 2 (μ-CN) 2 }(PF 6 ) 2 120 (dppm = Ph 2 PCH 2 PPh 2 ), which shows an impressive photophysical performance in solid state due to thermally activated delayed fluorescence (TADF), is used as a basic building block for the construction of higher luminescent nuclearities.…”
Section: Systems Composed By Metallacages Pd X L ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Costuas, Yam, and Lescop have reported a different approximation to the building of highly luminescent supramolecular moieties containing Pd(II) centers [ 109 , 110 ]. In these cases, the tetranuclear Cu(I) derivative {[Cu 2 (μ-dppm) 2 ] 2 (μ-CN) 2 }(PF 6 ) 2 120 (dppm = Ph 2 PCH 2 PPh 2 ), which shows an impressive photophysical performance in solid state due to thermally activated delayed fluorescence (TADF), is used as a basic building block for the construction of higher luminescent nuclearities.…”
Section: Systems Composed By Metallacages Pd X L ...mentioning
confidence: 99%
“…Further work showed that [Cu 8 Pd(CN) 8 (dppm) 8 ](PF 6 ) 2 121 can be obtained as different polymorphs arising from different sources [ 110 ]: (i) as minor components during the crystallization of the main component shown in Figure 33 , for which the only difference is the μ 3 -bonding mode of the central cyanide ligands; (ii) mechanical treatment of the major component; (iii) thermal heating of the main component giving an irreversible melting transition; and (iv) even from DFT calculations. Not surprisingly, the polymorphs only differ in subtle details of the molecular structure, but these small are translated into huge differences in photophysical properties, and strong enhancements of the luminescence are observed [ 110 ]. As detailed previously, the quantum yield of the main component is 2%.…”
Section: Systems Composed By Metallacages Pd X L ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous investigations conducted on related luminescent ‘Cu 6 ’ and ‘Cu 8 Pd 1 ’ assemblies have revealed that the crystal packing greatly influences the solid-state molecular conformations observed in single crystals and therefore the metric data and the solid-state photophysical properties of these derivatives. 58,59 Taking these aspects into account, indirect simulations of these packings were performed by constraining the copper atomic positions in the metallacycles to those of the X-ray structures. These partially constrained geometry optimizations lead to A opt-const (S 0 ) and B opt-const (S 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the fascinating structural flexibility and luminescence properties that can be associated with Cu( i )-based molecular assemblies, these derivatives exhibit appealing potential for designing such stimuli-sensitive materials, 1 and indeed attractive mechanochromic luminescent mononuclear or mainly polynuclear Cu( i ) complexes have been reported in recent years. 1,28,38,43,44,58…”
Section: Resultsmentioning
confidence: 99%